Computational chemistry introduction to the theory and applications of molecular and quantum mechanics - Lewars, Errol G.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
The second edition of this popular textbook has been revised to improve explanations and to add topics which were not featured in the first edition. It also contains extended, updated examples and references. The questions (the hallmark of a genuine textbook) at the end of each chapter fall into two classes: to test and reinforce the reader?s understanding, and to encourage deeper thought. As in the first edition, all pivotal statements and examples are supported by original literature references, and these have been updated to 2009 and 2010. Many calculations included by the author serve to illustrate and to show the scope of various methods. The main methodologies, e.g molecular mechanics, ab initio, semiempirical, and density functional theory (DFT), are introduced in a historical context (but without glossing over scientific detail) because the author believes that a scientific text should also be a humane exposition and not a collection of recipes. This textbook is intended for undergraduate and graduate students working in computational and theoretical chemistry courses and for researchers in universities and industry to whom computational chemistry may be useful. It may be used for self-study or with an instructor. Errol Lewars has done it again. The author of Modeling Marvels: Computational Anticipation of Novel Molecules has written a new edition of another of his highly interesting and informative books, one that interleaves and interweaves rigorous theory, computational protocol, dare I say classical chemistry, and biographical snapshots. Both the novice and practitioner will find much to enjoy and be educated by Lewars' decision to include easier questions, harder questions and answers that accompany the text." (Prof. Joel F. Liebman, University of Maryland, Baltimore County, UMBC, USA).
1. An outline of what computational chemistry is all about -- 2. The concept of the potential energy surface -- 3. Molecular mechanics -- 4. Introduction to quantum mechanics in computational chemistry -- 5. Ab initio calculations -- 6. Semiempirical calculations -- 7. Density functional calculations -- 8. Some "special" topics: (a) solvation, (b) singlet diradicals, (c) a note on heavy atoms and transition metals -- 9. Selected literature highlights, books, websites, software and hardware.
Electronic reproduction.
Keywords: Chemistry -- Data processing; Electronic books